Quality of Work Life and Praxis Humanism. The Perspective of Teachers in Yucatán, Mexico during the School Years (2020-2021) and (2023-2024) - Torales Herrera, Brenda (2025)
Introduction. It is suggested that, despite having overcome the pandemic recovery phase, this and the transition of the educational system back to its humanistic foundation origins resulted in various needs and concerns that unequally impacted the school community and, especially, the teaching staff, which could be affecting their quality of working life. Objective. To describe and compare the perspective of the teaching staff on their quality of working life from a humanistic praxis.Methodology. A qualitative approach was followed, and the information wascollected through interviews and questionnaires. For the data analysis, the Maxqda (2020) software and the content analysis technique proposed by Bardin (2002) were used. Results. It was found that the workload affected all teaching staff in both school years. Teaching staff with school-aged children showed greater effects on work-family balance, due to their role and family context. Likewise, it was highlighted that changes in labor policy during the health crisis resulted in lower well-being for the teaching staff of San José Tzal. Professional satisfaction materialized in acts of solidarity and extended performance beyond the school,driven by a deep understanding of the students’ family and community contexts. Conclusions. The humanistic praxis catalyzed an active reflection among the teaching staff that, although it confronted them with their precarious working conditions, simultaneously reaffirmed their vocational commitment to mitigate educational lag in the post-health crisis.